A Review of the Numerical Investigations of Jet-In-Hot-Coflow Burner With Reactor-Based Models - Li, Zhiyi; Parente, Alessandro (Frontiers in Mechanical Engineering, 2020)
Moderate or Intense Low-oxygen Dilution (MILD) combustion is considered as one of the most promising novel combustion technologies, as it ensures high efficiency and very low emissions (NO x and CO). Because of the high level of dilution, the system reactivity is reduced and the chemical time scale is increased compared to conventional flames. Therefore, combustion models accounting for finite-rate chemistry are needed to study the characteristics of such flames. Reactor based models, such as the Partially Stirred Reactor and the Eddy Dissipation Concept models have been successfully used to model MILD combustion. This article describes recent progress and developments in the application of reactor based models for the simulation of the jet-in-hot-coflow burners that emulate MILD combustion. The main objective is to provide an overview about the current state of the art of reactor based models for turbulence-chemistry interactions in MILD regime and outline future prospects for the further development of such models. The literature acknowledges both Reynolds Averaged Navier Stokes and Large Eddy Simulations studies, with various operating conditions as well as different fuels. The results indicate that it is necessary to include both the mixing and chemical time scales explicitly in the combustion model formulation. Because of the distributed reaction area, according to recent investigations, Large Eddy Simulation grid can be sufficient to resolve the MILD combustion reacting structures. The present review underlines the importance of finite rate chemistry in MILD combustion simulations, as well as of providing reliable estimation of the characteristic time scales.